Pengembangan Media Pembelajaran Infografis IPA Berbasis Canva untuk Meningkatkan Hasil Belajar Siswa - Sevi Ristanti; Barokah Isdaryanti (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to develop, test the feasibility, and effectiveness of Canva-based infographic learning media. This type of research and development (R&D) development research with the ADDIE development model, namely analysis, design, development, implementation, and evaluation). The research subjects were fourth grade students totaling 25 students, data collection techniques with observation, interviews, questionnaires, and documentation data. The results of media expert validation show a percentage value of 88.3% very feasible category, material experts with a percentage value of 86.66% very feasible category. Based on the pretest-posttest results, it is known that Canva-based infographic media is effective in improving student learning outcomes, which is indicated by an increase in the average pretest score from 52 to 80 on the posttest, with an N-Gain test result of 0.58 in the moderate category. Based on the response questionnaire distributed, a very positive response was obtained from teachers and students. From these results, it can be concluded that Canva-based infographic learning media is effective in improving student learning outcomes and is feasible and practical to use in IPAS learning on respiratory system material in grade V SD Negeri Tambakaji 05.